(untitled) - James R Craig (Englewood Cliffs, New Jersey, 1988)
The book offers knowledges of earth, mineral, environmental, or related sciences at the higher level. It presents inorganic material resources that are traditionally part of the disciplines of geology, mineralogy, and soil science. Thus, metals, industrial rocks and minerals, chemical minerals, water, and soil are all discussed and length. Major sections are devoted to fossil fuels such as coal and oil and to nuclear power and alternative energy sources (solar, wind, wave, geothermal, etc.). There are also chapters dealing with the sources, exploitation, and utilization of these particular resources and chapter dealing with more general questions concerning historical and environmental aspects of Earth resources and with the questions of resources for the future. In addition, there is an extensive glossary and appendices to help those unfamiliar with the terminology and some of the concepts used
Keywords: environmental policy,natural resources